Analisis Pengaruh Budaya Organisasi Terhadap Employee Engagement Dengan Kepuasan Kerja Sebagai Variabel Intervening - Humairoh Humairoh; Wardoyo Wardoyo (Universitas Multimedia Nusantara, 2017)
Human capital resources are essential to enhance performances and to sustain life cycles of a company. Organizational culture, job satisfaction and employee engagement are key factors of human resources. The objectives of this study were to describe and analyse the influence of organizational culture to employee engagement; to describe and analyse the influence of organizational culture to job satisfaction; to describe and analyse the influence of job satisfaction to employee engagement; and to describe and analyse organizational culture to employee engagement with job satisfaction as intervening variable. The hyphothesis of this study were: (i) the organizational culture has a positive influence to employee engagement, (ii) the organizational culture has a positive influence to job satisfaction, and (iii) the organizational culture has a positive influence to employee engagement with job satisfaction as intervenning variable. This study was a causal research to obtain evidences of causal relationships. The technique sampling applied was a cluster random sampling method with questionnaires as the instrument to collect data whose result processed using method Scala Likert Summated Rating (LSR) with score 1 – 4. Respondents of this research were employees of PT Krakatau Bandar Samudera (KBS) – a port services company in the Province of Banten. Respondents of 155 employees were interviewed based on statements in the quetionnaires. This research used technique of path analysis using SPSS software version 20.. The results of this research indicated that organizational culture has a positive influence to employee engagement, job satisfaction has a positive influence on employee engagement, and organizational culture has a positive influence on employee engagement through job satisfaction as an intervening variable. Keywords: Organizational Culture, Job Satisfaction, Employee Engagement